Kapasitas Informasi, Motivasi dan Keterampilan Berperilaku Kalangan Muda dalam Pencegahan HIV/AIDS - Rokhani, Rokhani; Mustofa, Akhmad (Lembaga Teewan Journal Solutions, 2026)
This study aimed to analyze the relationship between information capacity, personal motivation, social motivation, and behavioral skills in HIV/AIDS prevention among young people. A quantitative study with a cross-sectional design was conducted involving 108 students from a private university in Semarang City selected through proportional random sampling. Data were collected using structured questionnaires and analyzed using descriptive statistics and inferential analysis to examine the relationships among variables. The findings showed that most participants had high information capacity, high personal motivation, low social motivation, and good behavioral skills in HIV/AIDS prevention. However, no statistically significant relationship was found between information capacity, personal motivation, social motivation, and behavioral skills related to HIV/AIDS prevention (p > 0.05). These findings indicate that improving knowledge and motivation alone may not be sufficient to promote preventive behaviors among young people. This study concludes that information capacity, personal motivation, social motivation, and behavioral skills were not significantly associated with HIV/AIDS prevention behavior. The novelty of this study lies in examining the integrated Information–Motivation–Behavioral Skills (IMB) model among Indonesian university students and demonstrating that these constructs alone may not adequately explain HIV/AIDS preventive behavior, highlighting the need to consider additional contextual and environmental factors.